2010
DOI: 10.1177/1075547010378658
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Scientists’ Public Outreach and Engagement Activities

Abstract: Science communication research has tended to focus on the perceptions of the public and has often neglected the views of scientists. This article analyzes public outreach and engagement attitudes and activities of women scientists; it is based on a case study conducted in Switzerland. The survey results found that attitudes toward public outreach and engagement activities are the same among men and women scientists, but that activities are done significantly more often by men scientists than by women scientist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 22 publications
2
42
0
3
Order By: Relevance
“…8,35,38,46 This contention is also evident in the age profile of the 18 most visible scientists identified in this study who were between 45 and 69 years old, with an average age of 52 (and only two researchers younger than 50). These findings are in line with the higher levels of public communication involvement of more senior researchers who have been demonstrated in, for example, Switzerland 36 and Argentina 37 . It has also been suggested that scientists should earn a scientific reputation before venturing out into the public arena.…”
Section: Public Visibility Increases With Senioritysupporting
confidence: 74%
See 1 more Smart Citation
“…8,35,38,46 This contention is also evident in the age profile of the 18 most visible scientists identified in this study who were between 45 and 69 years old, with an average age of 52 (and only two researchers younger than 50). These findings are in line with the higher levels of public communication involvement of more senior researchers who have been demonstrated in, for example, Switzerland 36 and Argentina 37 . It has also been suggested that scientists should earn a scientific reputation before venturing out into the public arena.…”
Section: Public Visibility Increases With Senioritysupporting
confidence: 74%
“…A number of factors -including age 35 , gender 36 , position 37 , discipline 38 and organisational culture 39 -have been shown to influence if and how scientists communicate with public audiences. As such, the aim of the current study was to identify publicly visible scientists in South Africa, along with relevant background information about them that might help explain their public visibility.…”
Section: Methodsmentioning
confidence: 99%
“…4 There is also an emerging literature that explores scientists and public engagement, through examination of a range of factors such as demographics, seniority, academic achievement, discipline, and personal motivations and attitudes 5 (e.g. Poliakoff and Webb 2007;Jensen et al 2008;Dunwoody et al 2009;Besley and Nisbet 2013;Besley et al 2012;Jensen 2011;Kreimer et al 2011;Wilkinson et al 2011;Torres-Albero et al 2011;Crettaz von Roten 2011). Across all these fields, however, there is a tendency to treat Bscience^in an undifferentiated way, for example, not distinguishing among the different institutional and political contexts in which scientists work and communicate with the public.…”
Section: Introductionmentioning
confidence: 96%
“…However, particle physics favours the term "outreach", as is evident from the creation of CERN's "Education, Communication and Outreach" team following a restructure at the laboratory earlier this year and the existence of organisations such as the International Particle Physics Outreach Group (IPPOG). Crettaz von Roten further lends support for the use of this term, noting that it is often used to refer to all science-communication activities "designed for an audience outside academia" [3].…”
Section: 3defining Outreachmentioning
confidence: 99%
“…Of course, "engagement" cannot exist without an "understanding" of science, which is why Crettaz von Roten identified three aspects to engagement, which also show the evolution of the field [3]:…”
Section: Introductionmentioning
confidence: 99%